Textbook of industrial pharmacognosy - Kashi, Anusuya R. (Hyderabad University Press, 2013)
This book is designed for undergraduate pharmacy students and provides both contemporary and comprehensive information on herbal drugs. The first three chapters-herbal drug industry, patents and intellectual property rights and standardization of herbal drugs are new and have been culled from diverse sources. The book provides current information and is organized in a format that enables students to focus on the important aspects.
Keywords: PHARMACOGNOSY